Hematopoietic Multipotent Progenitors and Plasma Cells: Neighbors or Roommates in the Mouse Bone Marrow Ecosystem? - Bonaud, Amélie; Lemos, Julia P.; Espéli, Marion; Balabanian, Karl (Frontiers in Immunology, 2021)
The bone marrow is a complex ecosystem in which hematopoietic and non-hematopoietic cells reside. In this review, we discuss the bone marrow niches in mice that facilitate the survival, maintenance, and differentiation of cells of hematopoietic origin based on the recent literature. Our review places a special focus on the hematopoietic multipotent progenitors and on plasma cells, corresponding to the last stage of the B-cell lineage, that play a key role in the humoral memory response. We highlight the similarities between the microenvironments necessary for the establishment and the maintenance of these two immune cell subsets, and how the chemokine CXCL12/CXCR4 signaling axis contributes to these processes. Finally, we bring elements to address the following question: are multipotent progenitors and plasma cells neighbors or roommates within the bone marrow?